HIV a literary review on treatment, healing and the LGBTQIA+ population (Research, Society and Development, 2022)
We developed a literature review with the aim of promoting an analysis regarding the public and integrative view of the LGBTQIA+ population in relation to HIV and AIDS, with cases dating back to the 70s, HIV has two subtypes that cause infection called HIV- 1 and HIV-2, the virus today has three stages of infection from the asymptomatic stage to the AIDS stage where the individual is more vulnerable to opportunistic infections. HIV is an infection that has reached the stage of a pandemic in the world, which demonstrates that the infection is no longer restricted to what were considered risk groups, reaching the population in general. Concomitant with the spread of HIV/AIDS in the population over the decades, new treatment options were being developed, which increased survival and improved the quality of life of those affected and thereby reduced the fear of early death and allowed permanence social relationships in general, however, there remains the need to know the psychic aspects involved, both in the discovery phase and in the treatment phase and how having psychological help can contribute to a better coexistence in society. The LGBTQIA+ public suffers discrimination because it is somehow associated with individuals with HIV and it is a subject that has been much discussed, because the HIV virus does not choose a sexual option, all individuals in society regardless of race, color, and sex are subject to AIDS.